A Hairpin Loop at the 5′ End of Influenza A Virus Virion RNA Is Required for Synthesis of Poly(A)(+) mRNA In Vitro - Pritlove, David C. (American Society for Microbiology, 1999)
We present evidence, based on extensive mutagenesis, that a hairpin loop at the 5′ end of influenza A virus virion RNA (vRNA) is required for the synthesis of polyadenylated mRNA from model vRNA templates in vitro. The hairpin loop, which we term the vRNA 5′ hook, contains a stem of 2 bp formed by the second and third residues pairing with the ninth and eighth residues, respectively, and a 4-nucleotide loop composed of the intervening residues 4 to 7. Disruption of the base pairs of the vRNA 5′ hook by introducing point mutations prevented polyadenylation, except in two mutants where a G-U base pair reformed. The polyadenylation activity of point mutants could be rescued by constructing double mutants with reformed base pairs in the stem of the vRNA 5′ hook. These results suggest that base pairing rather than a particular nucleotide sequence was critical. We also show that mutation of the analogous region in the 3′ arm of vRNA did not interfere with the synthesis of polyadenylated mRNA, suggesting that a hook structure in the 3′ arm is not required for transcription of polyadenylated mRNA in vitro.